2001
DOI: 10.1152/jappl.2001.90.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of humoral and peripheral vascular responses during graded exercise in heart failure

Abstract: We hypothesized that performance of exercise during heart failure (HF) would lead to hypoperfusion of active skeletal muscles, causing sympathoactivation at lower workloads and alteration of the normal hemodynamic and hormonal responses. We measured cardiac output, mean aortic and right atrial pressures, hindlimb and renal blood flow (RBF), arterial plasma norepinephrine (NE), plasma renin activity (PRA), and plasma arginine vasopressin (AVP) in seven dogs during graded treadmill exercises and at rest. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 25 publications
(36 reference statements)
4
84
0
Order By: Relevance
“…So, in summary, alteration of all three mechanisms may contribute to the lack of increase in LV contractile state with MMR activation in HF. Our results are in accordance with previous investigations where it was shown that the muscle metaboreflex is still capable of generating a pressor response during mild to moderate exercise in HF dogs, although the mechanisms of this response are different compared with those observed in normal conditions (11,12). In HF conditions, the pressor response must depend on responses within the peripheral vasculature (vasoconstriction), because the increase in CO is virtually abolished.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…So, in summary, alteration of all three mechanisms may contribute to the lack of increase in LV contractile state with MMR activation in HF. Our results are in accordance with previous investigations where it was shown that the muscle metaboreflex is still capable of generating a pressor response during mild to moderate exercise in HF dogs, although the mechanisms of this response are different compared with those observed in normal conditions (11,12). In HF conditions, the pressor response must depend on responses within the peripheral vasculature (vasoconstriction), because the increase in CO is virtually abolished.…”
Section: Discussionsupporting
confidence: 92%
“…No exercise was performed in that study. Previous studies from our laboratory (11,12) have shown that in pacing-induced HF dogs, when MMR was activated during mild to moderate dynamic exercise, the increase in CO was significantly attenuated and the pressor response was more dependent on responses within the peripheral vasculature that result from increases in sympathetic outflow as well as the secretion of vasoactive hormones. In the present study after the induction of HF, we observed that SV and end-systolic pressure decreased.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Briefly, the right ventricular pacing electrodes were connected to an external pacemaker set at 240 -250 beats/min for ϳ30 days. After an induction of modest HF (defined as resting tachycardia, reduced CO, SV, and maximum and minimum first derivative of left ventricular pressure) as described in our previous studies (8,9,14,28), the experiments were repeated. The pacemaker was turned off before each experiment, and data collection began after the hemodynamic variables had reached steady state (ϳ30 min).…”
Section: Methodsmentioning
confidence: 99%